2016
DOI: 10.1021/jacs.5b12741
|View full text |Cite
|
Sign up to set email alerts
|

Photoinitiated Reactivity of a Thiolate-Ligated, Spin-Crossover Nonheme {FeNO}7 Complex with Dioxygen

Abstract: The nonheme iron complex, [Fe(NO)(N3PyS)]BF4, is a rare example of an {FeNO}7 species that exhibits spin-crossover behavior. The comparison of X-ray crystallographic studies at low and high temperatures and variable-temperature magnetic susceptibility measurements show that a low-spin S = 1/2 ground state is populated at 0–150 K, while both low-spin S = 1/2 and high-spin S = 3/2 states are populated at T > 150 K. These results explain the observation of two N–O vibrational modes at 1737 and 1649 cm−1 in CD3CN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 74 publications
(200 reference statements)
0
40
0
Order By: Relevance
“…We previously showed that 1 exhibits spin-crossover behavior, with a low-spin ( S = 1/2) ground state and a thermally accessible high-spin ( S = 3/2) excited state. 8b The low-spin species exhibited a ν (N—O) at 1641 cm −1 at cryogenic temperatures, whereas the high-spin ( S = 3/2) ν (N–O) is observed at 1737 cm −1 above 150 K (CD 3 CN). The RR spectrum of 3 (Figure 4) (λ exc = 647 nm) reveals a prominent, broad band at 1588 cm −1 that shifts to 1518 cm −1 upon substitution with 15 N 18 O; this 70-cm −1 downshift is in agreement with an N-O harmonic oscillator model (calculated Δ ν = −71 cm −1 ), confirming the assignment of this band to the N-O stretch of the new {FeNO} 8 species.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…We previously showed that 1 exhibits spin-crossover behavior, with a low-spin ( S = 1/2) ground state and a thermally accessible high-spin ( S = 3/2) excited state. 8b The low-spin species exhibited a ν (N—O) at 1641 cm −1 at cryogenic temperatures, whereas the high-spin ( S = 3/2) ν (N–O) is observed at 1737 cm −1 above 150 K (CD 3 CN). The RR spectrum of 3 (Figure 4) (λ exc = 647 nm) reveals a prominent, broad band at 1588 cm −1 that shifts to 1518 cm −1 upon substitution with 15 N 18 O; this 70-cm −1 downshift is in agreement with an N-O harmonic oscillator model (calculated Δ ν = −71 cm −1 ), confirming the assignment of this band to the N-O stretch of the new {FeNO} 8 species.…”
mentioning
confidence: 96%
“…Reduction of {FeNO} x (x = 6, 7) species to the reactive {FeNO} 8 or {FeN(H)O} 8 states is often invoked as a prerequisite for N 2 O formation in enzymatic systems. There has been considerable interest in the preparation and characterization of {FeNO} 8 /{FeN(H)O} 8 model complexes, 5 but their synthesis is challenging because of their instability.…”
mentioning
confidence: 99%
See 3 more Smart Citations